HUBUNGAN KONDISI PSIKOLOGIS PENERIMA PERSETUJUAN GENERAL CONSENT DENGAN PEMAHAMAN TENTANG HAK PASIEN RUMAH SAKIT SESUAI UNDANG – UNDANG NOMOR 44 TAHUN 2009 PASAL 32 DI RS AISYIYAH KUDUS TAHUN 2016 - muhammad purnomo ((IJP) Indonesia Jurnal Perawat, 2017)
Feeling depressed hearts Facing A problem, Could Be stress. Stress is a prayer One Form of Psychological Disorders That often attacked by the Human Rights of Patients and Families is information that was provided by parties Hospital Patients showed to the family OR That includes information on the rights and Obligations Patients And listed hearts legislation. Laws - laws revoked them is law no. 44 year 2009 concerning hospitals, law number 29 of 2004 about practice of medicine and some other gatra regulations. on research singer took the title of psychological condition common consent agreement receiver with about understanding patient rights hospital under the act - law no. 44 year 2009 article 32. singer study is a quantitative research using analytical description with with sectional study design. the example used by 35 respondents. obtained results 9 respondents (25.7%) believed the psychological condition of the less / decreased. from the results obtained rated spearman test (p value = 0.027 α = 0.05; r = 0374 value) can then be concluded that the ada relations psychological condition common consent agreement receiver with about understanding patient rights hospital under the act - law number 44 2009 article 32.